Acute Treatment of Isolated Posterior Cerebral Artery Occlusion: Single Center Experience - Cunha, B (2022)
Background and objectives: Randomized trials for mechanical thrombectomy (MT) excluded patients with ischemic strokes due to isolated posterior cerebral artery occlusion (IPCAO), and there is no evidence for best acute treatment strategy in these patients. We aimed to assess the effectiveness and safety of MT in acute IPCAO. Methods: We retrospectively analyzed consecutive patients with acute stroke due to IPCAO submitted to MT and/or intravenous thrombolysis (IVT), between 2015-2019. Effectiveness outcomes (recanalization rate, first-pass effect, NIHSS 24h improvement and 3-month Modified Ranking Scale - mRS) and safety outcomes (complications, symptomatic intracranial hemorrhage (SICH) and 3-month mortality) were described and compared between groups. Results: A total of 38 patients were included, 25 underwent MT and 13 had IVT alone. Successful and complete recanalization were achieved in 68% and 52% of MT patients, respectively. NIHSS improvement at 24h was found in 56% of MT patients versus 30.8% of patients submitted to IVT alone (OR [95% CI]=2.86 [0.69-11.82]) and excellent functional outcome at 3 months (mRS≤1) was achieved in 54.2% of MT patients versus 38.5% in the IVT group (OR [95% CI]=1.60 [0.41-6.32]). Complications occurred in 3 (12%) procedures and there were no SICH. Mortality at 3 months was 20% in the MT group and 15.4% in patients submitted to IVT alone. Conclusions: Our results reflect a real-world scenario in a single center and seem to support the recently growing literature showing that MT is a feasible and safe treatment in IPCAO, with favorable effectiveness.